Historical and language-cultural dimensions of Nobel Gospel of 1520 - Ніка, Оксана Іванівна (Київський національний університет імені Тараса Шевченка, 2023)
A manuscript from the beginning of the 16th century from Noble (Pinsk County, which is now in Rivne oblast, Ukraine) was studied, representing the religious writing of the Grand Duchy of Lithuania in historical and language-cultural aspects. The afterword to the Nobel Gospel was analyzed, and the historical figures named in it were identified (Prince Fedor Ivanovich Yaroslavich, Bishop Jonah). Information about them was collected based on historical sources and scientific literature. The ‘Ruthenian’ edition of the Church Slavonic language, manifestations of the second South Slavic influence in the text, is characterized. The monument’s history information, now represented in the Library of the Vrublevsky Academy of Sciences of Lithuania (Lithuania), was systematized. The Nobel Gospel, which has not been the subject of scientific study until now, was analyzed during an interdisciplinary study. The historical context of the monument’s creation based on the afterword is analyzed. Its temporal and spatial localization, the possible sphere of operation, ancient storage of the rarity, scribes (Chivs), and historians were established. Prince Fedor Ivanovich Yaroslavich carried out charitable activities. He founded and supported churches and monasteries in the Pinsk District. The bishops of Pinsk and Turov, Vasian, and later Jonah, mentioned in the afterword, appealed to the king and received a “salary” letter stating that it should be their will and approval for the construction of churches and monasteries. The analyzed manuscript from Polissia was proved to reveal the book traditions of the 16th century and the eccentricity of the centers of rewriting texts of religious writing. The main manifestations of the second South Slavic influence in the orthography of the manuscript are characterized. Different orthographic and phonetic features of the ‘Ruthenian’ edition of the Church Slavonic language have been analyzed. Since the 60s of the 19th century, the manuscript from Polissia was transported to the Vilnius Public Library. The Manuscript Department was founded here, and the first descriptions of the monument were compiled.

Досліджено рукопис початку ХVІ століття із Нобля (Пінського повіту, нині Рівненська область, Україна), що репрезентує релігійне письменство Великого князівства Литовського в історичному і мовнокультурному аспектах. Проаналізовано післямову до Нобельського Євангелія і встановлено названі в ній історичні особи (князь Федір Іванович Ярославич, єпископ Йона), зібрано інформацію про них на основі історичних джерел і наукової літератури. Охарактеризовано 'руську' редакцію церковнослов'янської мови, вияви другого південнослов'янського впливу в тексті. Систематизовано інформацію про історію пам'ятки, яка зараз зберігається у Бібліотеці Академії наук Литви імені Врублевських (Литва). У ході міждисциплінарного дослідження проаналізовано Нобельське Євангеліє, що досі не було предметом наукового вивчення. Проаналізовано історичний контекст створення пам'ятки на основі післямови. Встановлено її часову та просторову локалізацію, можливу сферу функціонування і давнє зберігання раритету, переписувача (-чів), історичних осіб. Виявлено, що князь Федір Іванович Ярославич здійснював благодійницьку діяльність, фундував та підтримував церкви і монастирі в Пінському повіті. Розкрито, що єпископи Пінські та Туровські Васіан, а згодом і згаданий у післямові Йона зверталися до короля та отримали "жалованні" грамоти про те, що має бути їхня воля і благовоління на спорудження церков і монастирів. Доведено, що аналізований рукопис із Полісся розкриває книжні традиції ХVІ століття, відцентровість центрів переписування текстів релігійного письменства. Схарактеризовано основні вияви другого південнослов'янського впливу в орфографії рукопису. Проаналізовано окремі орфографічні та фонетичні ознаки 'руської' редакції церковнослов'янської мови. З'ясовано, що з 60-х рр. ХІХ століття рукопис із Полісся був перевезений до Віленської публічної бібліотеки, у якій було засновано Рукописний відділ та укладено перші описи пам'ятки.
Історичний і мовно-культурний виміри Нобельського Євангелія 1520 року
Keywords: linguistic Source Studies; Nobel Gospel; a manuscript; ‘Ruthenian’ editing of the Church Slavonic language; Second South Slavic Influence; лінгводжерелознавство; Нобельське Євангеліє; рукопис; 'руська' редакція церковнослов'янської мови; другий південнослов'янський вплив